Formation from direct oxidation of H-2 and destruction by decomposition/hydrogenation of H2O2 over Pd/C catalyst in aqueous medium containing different acids and halide anions - Choudhary, Vasant R.; Samanta, Chanchal; Jana, Prabhas (Applied Catalysis A-General, 2007)
Direct oxidation of H-2 by O-2 to H2O2 and decomposition/hydrogenation of H2O2 (at 27 degrees C and atmospheric pressure) over Pd/C catalyst in an aqueous acidic reaction medium have been thoroughly investigated using different mineral acids (viz. 0.1 N H2SO4, H3PO4, H3BO3, HNO3, HCl, HBr or HI) and/or halide anions (viz. F-, Cl-, Br- or I-), covering their wide concentration range (0-24 mmol/dm(3)), in the reaction medium. In the absence of any externally added halide, appreciable H2O2 formation in the H2 oxidation occurred only when the medium contained HCl. However, the rates of H2O2 decomposition and hydrogenation are greatly reduced because of the presence of any acid; the influence on the H2O2 decomposition was, however, much larger for the halo acids. In the presence of acid (0.1 N H3PO4 or H2SO4), the H-2-to-H2O2 formation reaction is greatly enhanced by the externally added halide anions up to their optimum concentrations. However, above the optimum halide anion concentration, it is inhibited more than the H-2-to-water formation (parallel) reaction, causing a decrease in both the H2O2 yield and selectivity. Whereas, the H-2 conversion and H2O2 destruction activities of the catalyst are decreased continuously with increasing the halide anion (except F-) concentration. Among the halides, chloride is the best halide promoter for Pd/C catalyst in the H-2-to-H2O2 oxidation. At the optimum Cl-concentration (5.4 mmol/dm(3)), both the H-2 conversion and H2O2 yield are passed through a maximum and the H2O2 decomposition is greatly inhibited with increasing the phosphoric acid concentration. In the absence of either the chloride anions or the acid (or both) in the reaction medium, only a little or no H2O2 is formed in the H-2 oxidation and also the rate of H2O2 destruction is very fast, particularly in the presence of H-2; the rapid destruction of H2O2 is mainly due to its decomposition rather than its hydrogenation. The best H-2-to-H2O2 oxidation results are obtained at the optimum concentrations of both the acid and halide anions. In the presence of acid and chloride (or bromide) promoter, the H2O2 hydrogenation dominates the H2O2 destruction and hence the net H2O2 formation is mainly controlled by the H2O2 hydrogenation. (c) 2006 Published by Elsevier B.V.
Keywords: H2O2 decomposition; H2O2 hydrogenation; halide anion promoters; Hydrogen peroxide; oxidation of H-2-to-H2O2; Pd/C catalyst